2021
DOI: 10.1001/jamapediatrics.2021.1050
|View full text |Cite|
|
Sign up to set email alerts
|

Maternal and Neonatal Morbidity and Mortality Among Pregnant Women With and Without COVID-19 Infection

Abstract: IMPORTANCE Detailed information about the association of COVID-19 with outcomes in pregnant individuals compared with not-infected pregnant individuals is much needed. OBJECTIVE To evaluate the risks associated with COVID-19 in pregnancy on maternal and neonatal outcomes compared with not-infected, concomitant pregnant individuals. DESIGN, SETTING, AND PARTICIPANTSIn this cohort study that took place from March to October 2020, involving 43 institutions in 18 countries, 2 unmatched, consecutive, not-infected w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

58
877
13
32

Year Published

2021
2021
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 1,135 publications
(1,132 citation statements)
references
References 44 publications
58
877
13
32
Order By: Relevance
“… 4 Studies also showed an increased risk of pregnancy complications — including preterm birth, cesarean delivery, and preeclampsia — associated with Covid-19 infection during pregnancy. 5 Therefore, clinicians relied on developmental and reproductive animal data from Moderna that showed no safety concerns, and there was no biologically plausible reason that the mRNA technology would be harmful in pregnancy. Pregnant women were counseled to consider the available evidence and make personal decisions about vaccination in the absence of human safety data.…”
mentioning
confidence: 99%
“… 4 Studies also showed an increased risk of pregnancy complications — including preterm birth, cesarean delivery, and preeclampsia — associated with Covid-19 infection during pregnancy. 5 Therefore, clinicians relied on developmental and reproductive animal data from Moderna that showed no safety concerns, and there was no biologically plausible reason that the mRNA technology would be harmful in pregnancy. Pregnant women were counseled to consider the available evidence and make personal decisions about vaccination in the absence of human safety data.…”
mentioning
confidence: 99%
“…10 An international study collected outcomes of 706 pregnant mothers with SARS-CoV-2 infection during pregnancy and their newborns from 18 developed and developing countries. 11 Results from this large-scale study demonstrated that pregnant women with COVID-19, compared with those without COVID-19, were at a substantially increased risk of severe pregnancy complications and death. Interestingly, several cohort studies conducted in the USA have found that the majority of pregnant women with SARS-CoV-2 infection were either asymptomatic or had mild symptoms.…”
Section: Introductionmentioning
confidence: 83%
“…20 24 The large-scale international investigation found that infants born to women with COVID-19 during pregnancy had a significantly higher risk of severe perinatal mobility and mortality. 11 These risks remained significant after adjusting for prematurity, indicating a direct effect of COVID-19 on the infants.…”
Section: Introductionmentioning
confidence: 96%
“…There are still conflicting reports; and some methodological limitations have been addressed, such as COVID-19 testing only in symptomatic pregnancies and at delivery time, a lack of control for confounder factors (such as age, comorbidities, multiparity etc. ), limited comparisons with non-pregnant women, and an underrepresentation of pregnancies diagnosed with COVID-19 in early pregnancy [12,142]. Therefore, we here summarize the most concise data reported until June 2021.…”
Section: Maternal and Fetal Outcomes Of Covid-19mentioning
confidence: 96%